Systematic Literature Review for the Effect of Ecolabelling on Purchase Intention - Narendra, Roberto Gallant (Syntax Corporation, 2025)
Ecolabelling has become an innovation in green marketing that many companies have been adopting recently. This study aims to explore the role of ecolabelling in influencing customer purchase intention toward environmentally friendly products using a systematic literature review method. Based on an analysis of 15 indexed international journals, it was found that ecolabelling plays a crucial role as a quality and trust marker, reducing information asymmetry and enhancing purchase intention. Factors such as environmental awareness, customer knowledge, and effective information dissemination through social media or digital technology strengthen the impact of ecolabelling. Additionally, ecolabelling enhances brand image and product quality perception, making them more appealing to customers. This study concludes that ecolabelling is an effective marketing tool to promote sustainability and recommends increasing consumer education, label standardization, and leveraging digital technology in ecolabel promotion.